Grassland restoration in northern China is far from complete: evidence from carbon variation in the last three decades. Issue 4 (3rd April 2017) - Ma, Anna; He, Nianpeng; Xu, Li; Wang, Qiufeng; Li, Meiling; Yu, Guirui
Abstract: Ecosystem restoration requires considering both above‐ground biomass (AGB) and soils, and the latter is even more essential due to the importance and restoration difficulty of soil organic matter (SOM). Remote sensing studies have shown that AGB has recovered in the grasslands of northern China, but the recovery of soil organic carbon (SOC) or SOM is still unclear. Here, based on the published data between the 1980s and 2014, we used the variation in carbon (C) density observed in the vegetation and soils of four regions across northern China as integrative indicator to explore grassland restoration. Overall, northern Chinese grasslands were a weak carbon source (−14 Tg C), although C density in AGB and below‐ground biomass increased on average by 0.019 and 0.224 kg C/m 2, respectively, during the period considered in the present study. Unexpectedly, SOC density in the 0–20 cm soil layer decreased by 0.193 kg C/m 2 on average, and all regions registered a decrease in SOC, although values differed among them. Our findings were consistent with previous evaluations using remote sensing and with the idea that vegetation in northern China has been restored. However, SOC has not been restored, and given its importance for sustaining nutrient supply and water conservation, as well as the high difficulty of SOC restoration, grassland restoration in northern China is still far from being achieved.